Brightness and Contrast Modification in Ultrasonography Images Using Edge Detection Results - Retno Supriyanti; Suwitno Suwitno; Yogi Ramadhani; Haris Budi Widodo; Tutik Ida Rosanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Currently, ultrasonography device become an important equipment for supporting diagnosis in diesases. Unfortunetaly, a lot of ultrasonography images do not provide enough information for supporting diagnosis especially images produced by low-resolution ultrasonography. It is caused by image quality that has been produced is inadequate because of noise. This research aims to improve image quality by modifying brightness and contrast to the edge detection algorithms. By modifying the brightness and contrast will cause the value of standard deviation of the ultrasonography image is lowered. Raising setting values will cause deviation standard value becomes smaller, and also the result of standard deviation is inversely proportional to the value of RMSE.  The results show that this modification can improve image quality by reducing noise significantly.